The Correlation Between Salmonella typhi Associated Gallstone Formation and Gallbladder Cancer - Al-Sanjary, Sahira I.H.; Al-Rawi, Amera Mahmood M. (Iraqi Journal of Science, 2022)
The current research focused on the detection of Salmonella typhi and its relationship with the formation of gallstone and gall bladder cancer. Samples were collected from patients aged between 32-67 years (males and females) in Mosul city hospitals. The samples included 30gallbladder fresh tissues from patients suffering from gallstone and 20 formalinfixed-paraffin embedded (FFPE) gallbladder tissue from patients confirmed with gallbladder cancer. The results showed that 33% S. typhi isolates were diagnosed from the tissue samples using conventional methods, biochemical tests and Vitek2. All fresh tissues samples gave positive PCR results for the presence of FliC-d and CdtB genes and 46% positivity for S. typhi compared with conventional methods, 64% for females, 35% for males and 40 % positive in the gallbladder cancer of which 62% were females and 37%males.